Analisis Arus Jenuh dan Panjang Antrian pada Simpang Bersinyal: Studi Kasus di Jalan Dr. Sutomo-Suryopranoto, Yogyakarta - Rahayu, Gati; Rosyidi, Sri Atmaja P; Munawar, Ahmad (Universitas Muhammadiyah Yogyakarta, 2009)
The aim of this paper is to analyse the delay length based on MKJI (1997). A case study was conducted on a signalized junction of Dr.Sutomo-Suryopranoto road, Yogyakarta. The correction was carried out on coefficient of basic saturation flow in ranging from 600 to 2200. Therefore, the predicted (from MKJI 1997) and measured delay length was compared. The results show that the coefficient on basic saturation flow calculation needs to be modified in the range of 600 to 2200 in order to find the similar length of the delay between prediction and field measurement. Passenger car unit (PCU) unit for motorcycle from MKJI (1997) was also corrected from 0.2 to 0.15.Â